Strategi Pengembangan Ekowisata Mangrove Pomako di Kabupaten Mimika Provinsi Papua Tengah - Rantetandung, Diantika; Aksa, Kamran; Taking, Muhammad Idris (Fakultas Teknik Universitas Bosowa, 2023)
The purpose of this study was to find out what factors have caused the undeveloped mangrove pomako ecotourism, as well as to find out the development strategy for the Pomako mangrove ecotourism in Mimika Regency, Central Papua Province. This research is a descriptive research using qualitative methods. Data collection techniques are observation, interviews, and distributing questionnaires. For factor analysis of mangrove ecotourism development using chi square analysis, as well as analysis of mangrove ecotourism development strategies using swot analysis by taking 92 (ninety two) respondents. From the results of the analysis, it shows that the direction for the development of mangrove ecotourism, Pomako, is the SO strategy, utilizing strengths and optimizing existing opportunities.